2011
DOI: 10.1134/s0021364011150045
|View full text |Cite
|
Sign up to set email alerts
|

Flat bands in topological media

Abstract: Topological media are systems whose properties are protected by topology and thus are robust to deformations of the system. In topological insulators and superconductors the bulk-surface and bulk-vortex correspondence gives rise to the gapless Weyl, Dirac or Majorana fermions on the surface of the system and inside vortex cores. Here we show that in gapless topological media, the bulk-surface and bulk-vortex correspondence is more effective: it produces topologically protected gapless fermions without dispersi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
311
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(331 citation statements)
references
References 46 publications
19
311
0
1
Order By: Relevance
“…We choose τ to be of the order of two times the level spacing of the bound states ǫ 1 , Eq. (12). Figures 5 and 6 show the broadened LDOS for the two pairing symmetries.…”
Section: Local Density Of Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose τ to be of the order of two times the level spacing of the bound states ǫ 1 , Eq. (12). Figures 5 and 6 show the broadened LDOS for the two pairing symmetries.…”
Section: Local Density Of Statesmentioning
confidence: 99%
“…The non-trivial topology gives rise to a multitude of interesting phenomena [1][2][3][4][5][6][7][8] , in particular subgap states in vortex cores and protected gapless edge modes that can carry quantized thermal current and particle current. Probably the most prominent example of a chiral superconductor is the spin-triplet (p x ± ip y )-wave state, which is believed to be realized in Sr 2 RuO 4 9,10 , in the A phase of superfluid 3 He [11][12][13] , and in two-dimensional cold atomic gases 14 . Spin-polarized (p x ± ip y )-wave superconductors support nondegenerate Majorana zero-energy modes localized at vortex cores [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Flat-band ferromagnetism has been studied first by Lieb [16] and, subsequently, by Tasaki and Mielke [17][18][19][20]. More recently it has been shown that the high density of states of flat bands enhances the superconducting critical temperature [21,22]. Indeed, for fixed interaction strength, the flat-band dispersion provides the maximal critical temperature within mean-field BCS theory [23].…”
mentioning
confidence: 99%
“…Thus, the conduction band has a very flat pocket of a size p ∼ γ/v around the K and K points, and this pocket becomes perfectly flat in the limit N → ∞, corresponding to 'rhombohedral graphite'. The emergence of this flat pocket has previously been discussed in [23,24]. Now consider the application of a vertical electric field leading to potential difference V between any 2 consecutive layers.…”
mentioning
confidence: 99%
“…On the top and bottom surfaces, there are undimerized lattice sites, which give rise to gapless surface states. The low energy single particle Hamiltonian for the surface states of an N layer graphene takes the form [23,24,26,27,30] …”
mentioning
confidence: 99%